Unraveling Intrinsic Motivation: The Key to Empowering Teacher Professional Growth - Dewi Mayangsari; Nur Aini Fardana Nawangsari; Nono Hery Yoenanto; Dewi Retno Suminar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study explores the pivotal role of intrinsic motivation in driving the professional development of early childhood education (ECE) and kindergarten teachers, focusing on how it influences their teaching practices, adaptability, and overall job satisfaction. Methodology: A qualitative approach with a case study design was employed, involving purposively selected ECE and kindergarten teachers from multiple schools. Participants had at least five years of teaching experience and demonstrated active engagement in professional skill development. Data were gathered through in-depth interviews and participatory observations and then analyzed using thematic analysis to uncover recurring patterns and insights. Main Findings: The study reveals that intrinsic motivation significantly shapes the professional growth of ECE teachers. Motivated teachers are likelier to adopt innovative teaching methods, integrate new technologies into their classrooms, and demonstrate resilience in managing challenges. They display a heightened sense of responsibility for their students’ holistic development and report greater job satisfaction. Moreover, intrinsic motivation fosters creativity and adaptability, enabling teachers to craft engaging learning experiences. This, in turn, positively impacts student outcomes, as intrinsically motivated teachers create dynamic, supportive environments that enhance student engagement and facilitate social-emotional growth. Novelty/Originality of the Study: Underexplored connection between intrinsic motivation and professional development in early childhood education. The study underscores the need for fostering intrinsic motivation in teacher training programs by linking teacher motivation to innovation, resilience, and student engagement. Furthermore, it provides actionable insights into designing interventions and policies prioritizing intrinsic drivers, contributing to sustainable teacher development and improved educational quality.